Polyester-tethered near-infrared fluorophores confined in colloidal nanoparticles: tunable and thermoresponsive aggregation and biomedical applications - Yang, Cangjie (2023)
Intricate assembly of multiple molecular chromophores assisted by protein scaffolds is essential in tuning the optical absorption and energy transfer in the light-harvesting complexes of the photosynthetic systems in nature. However, it remains a challenge to achieve such structural complexity and functionality in synthetic polymer-chromophore systems. Here, we report a series of polyester-tethered pyrrolopyrrole cyanine derivatives and their colloidal nanoparticles dispersed in water, which show tunable J- or H-aggregation excitonic coupling and near-infrared fluorescence by precise control of the polymer chain lengths, composition, and temperature. Moreover, the optimal fluorescence or photothermal effect of the J-aggregate nanoparticles enables broad applications in fluorescence or photoacoustic bioimaging and phototherapy.